PENGUJIAN KEMBALI FENOMENA MONDAY EFFECT DI BURSA EFEK INDONESIA - , Fahrurizal Laitupa ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to examine the day of the week effect (Monday effect) on stock returns as well as the related phenomenon with negative returns on Friday the previous week, and Rogalski effect on the Indonesian Stock Exchange 2007- 2012 period. The problem posed in this study are first, whether there is the day of the week effect (Monday effect) on stock returns in the Indonesian Stock Exchange